Novel mixotrophic micro-algae oil biodiesel in sustainable clean fuel development - Folayan Adewale Johnson; Bilal Patel (Results in Engineering)
Most of the present studies on micro-algae development focused on enhanced biomass productivity with limited information on the effects of growth modes and nutrients availability on the expected biofuel critical performance properties as well as development of sustainable technologies for micro-algae energy production.In this study, the biofuel properties of mixotrophic chlorella vulgaris micro-algae biomass that was synthesized by a nickel-doped calcium oxide heterogeneous catalytic transesterification process were investigated under standard laboratory procedures. The Ni-CaO solid catalyst was prepared by co-precipitation of calcium oxide (CaO) with hydrated nickel nitrate dopant (Ni (NO3)2.6H20 (nickel (II) nitrate hexahydrate). Carbon IV Oxide solvent in its supercritical states (SCCO2) was used for triacylglycerols (TAGs) extraction. Advanced structural and analytical spectroscopic techniques including SEM and XRD, GC-MSD and FTIR were used for catalyst, extracted lipids and biodiesel characterizations respectively.A lipid content of 47.60 ± 2.31 % which consists majorly of long chain mono-unsaturated fatty acids with few poly-unsaturated molecules was obtained from the SFE process. Interestingly, the Ni-CaO catalyst has superior catalytic power with a glyceride conversion efficiency of 98.6 % due to replacement of ca2+ with nickel transition metal ions in the CaO lattice which enhances better catalytic performance by increased active surface area and improved catalytic activities. The biodiesel has lower density and kinematic viscosity values of 0.858 g/cm3 at 15 °C and 3.61mm2/s at 40 °C. This promotes efficient fuel-air mixture and better atomization and combustion characteristics. Finally, the ester biofuel has higher cetane index and heating values of 55.6 and of 41.12 MJ/Kg respectively due to higher proportion of long chain and MUFAs in its ester structure. This inevitably promotes better ignition quality, lower fuel consumption, enhances superior fuel combustion and performance characteristics and reduced particulate matter emissions.